Counter Irritation - An Indigenous Healing Method Practiced in Nepal by Self Made Doctors: A Case Report - Mishra, SD; Joshi, P; Oram, PB; Prakash, Nairan (Journal of Universal College of Medical Sciences, 2013)
A rare case, wherein a brass pot adherent to the anterior abdominal wall in a 55 year old women as a result of counter irritant indigenous method of treatment for pain in rural and remote areas of Nepal is being reported. This would have led to grave consequences, if not treated timely DOI: http://dx.doi.org/10.3126/jucms.v1i2.8409 Journal of Universal College of Medical Sciences Vol.1(2) 2013: 37-38